Ethnicised Spectatorship in the Malaysian Film Nasi Lemak 2.0 - Ngo Sheau-Shi (Wacana Seni Journal of Arts Discourse, 2019)
Namewee, a contemporary filmmaker in Malaysia, has made himself increasingly popular since 2007 by criticising the government and posting racist remarks in social media. In 2011, Namewee produced and directed a controversial film: Nasi Lemak 2.0. Given the highly racialised and politicised backdrop of this work, this article intends to examine the subtext of the film as a significant cultural artefact used to reconstruct meaning and identity in the context of a multicultural, multi-ethnic and multi-religious Malaysian society. The main argument presented here is that the subtext of Nasi Lemak 2.0 offers a spectatorial position strongly linked to the Chinese male protagonist. This ethnicised spectatorship provides a symptomatic field with which to reconstruct and reinforce Malaysia's long held racial ideology which is rooted in the country's colonial past.